The Diversity of the Mitochondrial Outer Membrane Protein Import Channels: Emerging Targets for Modulation - Monika Mazur; Hanna Kmita; Małgorzata Wojtkowska (Molecules, 2021)
The functioning of mitochondria and their biogenesis are largely based on the proper function of the mitochondrial outer membrane channels, which selectively recognise and import proteins but also transport a wide range of other molecules, including metabolites, inorganic ions and nucleic acids. To date, nine channels have been identified in the mitochondrial outer membrane of which at least half represent the mitochondrial protein import apparatus. When compared to the mitochondrial inner membrane, the presented channels are mostly constitutively open and consequently may participate in transport of different molecules and contribute to relevant changes in the outer membrane permeability based on the channel conductance. In this review, we focus on the channel structure, properties and transported molecules as well as aspects important to their modulation. This information could be used for future studies of the cellular processes mediated by these channels, mitochondrial functioning and therapies for mitochondria-linked diseases.